(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the study of drama in literary criticism during the period of independence, changes in the Soga, the expansion of creative possibilities of writers, as well as how it stimulated the development of drama. In the years after independence, as in all fields of literary science, a number of studies on drama were conducted with a special focus on the contribution of Jadid literary figures to drama and its place in the development of this field. During this period, the dramas cite events related to the nationality, customs, and rituals of the Uzbek people, and an increase in the diversity of topics is noted.